2021
DOI: 10.1242/jeb.230342
|View full text |Cite
|
Sign up to set email alerts
|

Rapid toxin sequestration modifies poison frog physiology

Abstract: Poison frogs sequester chemical defenses from their diet of leaf litter arthropods for defense against predation. Little is known about the physiological adaptations that confer this unusual bioaccumulation ability. We conducted an alkaloid-feeding experiment with the Diablito poison frog (Oophaga sylvatica) to determine how quickly alkaloids are accumulated and how toxins modify frog physiology using quantitative proteomics. Diablito frogs rapidly accumulated the alkaloid decahydroquinoline within four days, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…It is possible that the ability to convert PTX 251D into aPTX 267A or sequester aPTX 267A to the skin has only been acquired in specific poison frog populations or species. The accumulation of both DHQ and PTX 251D in the liver, intestines, and skin, indicates that these tissues play an important role in the sequestration of alkaloids and echoes previous controlled feeding study results where frogs were only fed DHQ [14]. The liver and intestines are also important sites of alkaloid metabolism in mammals due to high levels of Cytochrome P450s [43][44][45].…”
Section: Plos Onesupporting
confidence: 79%
“…It is possible that the ability to convert PTX 251D into aPTX 267A or sequester aPTX 267A to the skin has only been acquired in specific poison frog populations or species. The accumulation of both DHQ and PTX 251D in the liver, intestines, and skin, indicates that these tissues play an important role in the sequestration of alkaloids and echoes previous controlled feeding study results where frogs were only fed DHQ [14]. The liver and intestines are also important sites of alkaloid metabolism in mammals due to high levels of Cytochrome P450s [43][44][45].…”
Section: Plos Onesupporting
confidence: 79%
“…7 ). Together these observations suggest that poison frogs have a means to prevent BTX and STX engaging the target Na V s. It is notable that other frogs resist STX poisoning ( Prinzmetal et al, 1932 ; Kao and Fuhrman, 1967 ; Mahar et al, 1991 ), and it is thought that the soluble STX-binding protein Sxph ( Mahar et al, 1991 ; Arbuckle et al, 2017 ; Yen et al, 2019 ) acts as a toxin sponge to sequester and neutralize the lethal effects of this and possibly other neurotoxins ( Mahar et al, 1991 ; Llewellyn et al, 1997 ; Arbuckle et al, 2017 ; Almabruk et al, 2018 ; Caty et al, 2019 ; O’Connell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lab feeding experiments have found that alkaloids accumulate primarily on the skin, although detectable quantities are also found in the liver and intestines [14]. This accumulation can occur within a few days [15,16], and is associated with changes in gene expression and protein abundance across tissues [15,16]. However, previous analyses of gene expression have been limited to comparing frogs with alkaloids to those without alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous analyses of gene expression have been limited to comparing frogs with alkaloids to those without alkaloids. [15-17], leaving a major gap in our understanding of how frog physiology changes in response to specific alkaloids rather than overall toxicity. Filling this knowledge gap is important because poison frogs carry many different alkaloid classes, each of which could potentially induce specific changes in physiology.…”
Section: Introductionmentioning
confidence: 99%